PENGARUH KOMPETENSI, INDEPENDENSI, DAN BUDAYA KERJA TERHADAP KINERJA AUDITOR INTERNAL PADA SEKDA KABUPATEN PANDEGLANG - Siti Masfufah; Ali Sandy Mulya (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
This study aims to examine the effect of competence, independence and work culture simultaneously on the performance of internal auditors. The population in the study was 177 people with a sample size of 64 people. The sampling technique was carried out by proportional random sampling technique. This study uses a quantitative method with the type of survey research and data analysis using multiple regression linear test. While the data collection technique using a questionnaire instrument. The results showed that there was a significant influence of competence, independence and work culture simultaneously on the performance of internal auditors at the Regional Secretariat of Pandeglang Regency. The findings of this study provide a contribution or contribution to the Regional Government of Pandeglang Regency in order to improve the competence, independence and work culture of internal auditors properly, so as to improve the performance of internal auditors in carrying out audits of financial statements at the Regional Secretariat of Pandeglang Regency.